2016
DOI: 10.1128/genomea.01338-16
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequence of the Acetogenic Bacterium Butyribacterium methylotrophicum DSM 3468 T

Abstract: Butyribacterium methylotrophicum DSM 3468T is an acetogenic methylotrophic, anaerobic, carbon monoxide–oxidizing bacterium that produces acetate, butyrate, and butanol. The genome consists of a single chromosome (4.3 Mb) and harbors 3,989 predicted protein-encoding genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Few other bacteria outside of this genus have been reported to be able to produce butanol. However, genome sequences of Eubacterium limosum SA11 [ 41 ] as well as KIST612 [ 42 ] and Butyribacterium methylotrophicum [ 43 ] reveal that such microorganisms do not possess sol operons of either clostridial type. Instead, aldehyde and alcohol dehydrogenase genes are found, whose encoded enzymes catalyze the production of butanol from butyryl-CoA.…”
Section: Discussionmentioning
confidence: 99%
“…Few other bacteria outside of this genus have been reported to be able to produce butanol. However, genome sequences of Eubacterium limosum SA11 [ 41 ] as well as KIST612 [ 42 ] and Butyribacterium methylotrophicum [ 43 ] reveal that such microorganisms do not possess sol operons of either clostridial type. Instead, aldehyde and alcohol dehydrogenase genes are found, whose encoded enzymes catalyze the production of butanol from butyryl-CoA.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrolyzed lactate seemed to be rapidly used for chain elongation since chain elongation products showed sustained production over time despite lactate monomers were depleted (Figure 2). Several bacteria harboring genes involved in lactate oxidation (lactate dehydrogenases, Ldh) and the RBO pathway such as C. tyrobutyricum (Wu et al, 2017), C. luticellarii (Poehlein et al, 2018) and members of the family Ruminococcaceae (Tao et al, 2017) including Caproiciproducens species (e.g., Bengelsdorf et al, 2019) were enriched in these conditions. C. tyrobutyricum is known as an efficient n-butyrate producer (Wu et al, 2017) but is not reported to produce longer carboxylates.…”
Section: Nzvi Affects Fermentation Conditions Shaping Microbiome Composition and Lactate Metabolismmentioning
confidence: 99%
“…Acetogens and their major characteristicsBernalier et al, 1996;Liu et al, 2008) Lesme et al, 1996 Liu et al, Zeikus et al, 1980;Lynd et al, 1982Bengelsdorf et al, 2016b) Abrini et al, 1994; K€ opke et al, 2011 Brown et al, 2014) CP010905 K€ opke et al, 2013 Riedel et al, 2015) K€ usel et al, 2000; Liou et al, 2005; G€ oßner et al, 2008; Jeong et al, 2014) Andreesen et al, 1970; Lux and Drake, 1992 Karl et al, 2017) Huhnke et al, 2008; K€ opke et al, 2011 Bengelsdorf et al, 2016a) Liou et al, 2005; Zhu et al, 2015)…”
mentioning
confidence: 99%